2023
DOI: 10.3390/nu15081942
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Different Types of Prebiotics in Infant Formula and Infection Rates: A Review

Abstract: Breastfeeding plays a protective role against infections, partially through the prebiotic effect of human milk oligosaccharides (HMOs). Aiming to mimic these beneficial capacities, there is an ongoing search to make infant formula closer to human milk, including by adding oligosaccharides. Over the past two decades, multiple studies have been published on different types of prebiotics and their role in reducing infection rates in infants. This review aims to answer the question of whether there is evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(149 reference statements)
0
0
0
Order By: Relevance
“…They bring the gastro-intestinal microbiota composition of these formula-fed infants closer to that of breastfed infants [58][59][60]. Secondary outcomes suggest an immunomodulatory effect, resulting in a decrease in inflammation, infections, and the prescription of antibiotics [61,62]. However, additional benefits on the efficacy of hydrolysates with added probiotics in the management of CMA have not been demonstrated [1].…”
Section: "Biotics" In Infant Formulamentioning
confidence: 99%
“…They bring the gastro-intestinal microbiota composition of these formula-fed infants closer to that of breastfed infants [58][59][60]. Secondary outcomes suggest an immunomodulatory effect, resulting in a decrease in inflammation, infections, and the prescription of antibiotics [61,62]. However, additional benefits on the efficacy of hydrolysates with added probiotics in the management of CMA have not been demonstrated [1].…”
Section: "Biotics" In Infant Formulamentioning
confidence: 99%
“…7 Galacto-oligosaccharides (GOS) and fructooligosaccharides (FOS) are historically the best studied, and supplementation with these seems to have a beneficial effect on infection rates. 8 However, it became recently possible to synthesize some of the ~200 HMOs chemically, via fermentation, and by enzymatic synthesis. Initially, two were added to infant formula: 2'-fucosyllactose (2'-FL) and lacto-N-neotetraose (LNnT).…”
mentioning
confidence: 99%
“…Unfortunately, the designs of these clinical studies are quite different, with different inclusion criteria, duration and amount of administration of oligosaccharides. 6,8 The primary outcomes of these trials focus on safety and tolerance, which have been confirmed. Secondary outcomes suggest a decrease of infections and prescription of antibiotics.…”
mentioning
confidence: 99%
See 2 more Smart Citations